NEGACIONISMO Y POSVERDAD EN EL DISCURSO POLÍTICO INSTITUCIONAL DE BOLSONARO - De Rosa, Gian Luigi (Cultura Latinoamericana, 2021)
The aim of this paper is to analyze Bolsonaro’s institutional political communication during the COVID-19 pandemic. The text develops the argument in two complementary phases: on the one hand, by analyzing the political language, that can be considered as specialized language, used in Bolsonaro’s institutional political communication.On the other hand, by focusing on the negationist and post-truth strategies of banalization of the pandemic present in official statements.